The Meaning of Labor Costs in The Development of Microenterprises in Poland - Rafał Rosiński (Communications of International Proceedings, 2022)
The aim of the article is to present the structure of labor costs in Poland and to analyze the fiscal conditions in the development of micro-enterprises in selected European Union countries. The introductory part uses the method of analyzing literature and legal acts, while the empirical part uses the method of examining documents based on Eurostat data, the World Bank's Doing Business report and own calculations. The analysis of the structure of labor costs in Poland has shown that it depends on the socio-economic policy of a given country, i.e. the social security system and the level and structure of income tax. When analyzing labor costs, first of all, attention should be paid to the minimum and average level of remuneration and the amount of non-wage costs, as they mainly determine the actual labor costs incurred by the employer, as well as the fiscal and legal conditions of the conducted business activity. Too fast growth of the minimum wage in relation to the average wage in the economy leads to wage pressure in other wage groups, which in turn significantly affects the profitability of running a business, and especially the development of micro-enterprises.
Keywords: labor costs; tax wedge; microenterprises.